INFLUENCE OF EASE OF USE, SECURITY AND RISK PERCEPTION ON INTEREST IN THE USE OF FINANCIAL TECHNOLOGY (FINTECH) PAYMENT LINKAJA SYARIAH : PENGARUH KEMUDAHAN PENGGUNAAN, KEAMANAN DAN PERSEPSI RISIKO TERHADAP MINAT PENGGUNAAN FINANCIAL TECHNOLOGY (FINTECH) PAYMENT LINKAJA SYARIAH - Maulida Swara Mahardika; Achmad Fauzi; Mardi Mardi (Yayasan Education and Social Center, 2021)
This study aims to determine the effect of ease of use, security and perceived risk on interest in use. This research was conducted at SMK PB Sudirman 2, this study used simple random sampling with 94 students as respondents using an online questionnaire with a linkert scale. The data is processed using SPSS v26 software. The research hypotheses were tested using multiple regression test, T-test and coefficient terminatedi. The results of this study indicate that there is a significant positive value between ease of use and interest in use, there is a significant positive effect between security and interest in use, there is a significant influence between perceived risk and interest in use. In this study, it was found that the easier it is, to provide security and guarantee the risk of using the Aja Syariah fintech payment link, the more interest it will be used. So that fintech payment companies should pay attention to these three factors